ANALISA KADAR Fe (III) AIR DI KECAMATAN TANGGULANGIN SIDOARJO - Ary Andini (UNUSA Press, 2018)
Decent water consumption has a characteristic of colorless, odorless, tasteless and no solids dissolved. One of the heavy metals that harmful to health body if excessive contained in water is Iron (III) (Fe(III). The method used in 2 main stages for analyzing of Fe (III) content those were determination standard curve and Fe (III) content in water with UV-Vis spectrophotometer at 480 nm wavelength. The result of this research showed that Fe (III) content in water in 10 samples of well water in Tanggulangin sub-district of Sidoarjo regency is quite feasible for daily use because the result of Fe (III) all sample were < 0,3 mg / L, its based on maximum concentration iron in drinking water as the Minister of Health Decree No.907 / MENKES / SK / VII / 2002.